2015
DOI: 10.1557/jmr.2015.102
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and properties of nanocrystalline Sn1−xCoxO2 based dilute magnetic semiconductors

Abstract: Monophasic Sn 1Àx Co x O 2 (x 5 0.05, 0.10, and 0.15) nanoparticles with tetragonal structure have been successfully synthesized by solvothermal method using oxalate precursor route. Powder x-ray diffraction and selected area electron diffraction studies confirmed highly crystalline cassiterite SnO 2 structure. The contraction of lattice constants confirmed the incorporation of Co 21 in SnO 2 host lattice. Hexagonal nanoparticles with average grain size of 8-13 nm have been formed. With the increasing Co conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Besides ZnO, TM doping has been done in other oxide materials viz.,CdO, In 2 O 3 , SnO 2 etc. also in their nanocrystalline form, however, most of them do not show any ferromagnetic behavior …”
Section: Introductionmentioning
confidence: 99%
“…Besides ZnO, TM doping has been done in other oxide materials viz.,CdO, In 2 O 3 , SnO 2 etc. also in their nanocrystalline form, however, most of them do not show any ferromagnetic behavior …”
Section: Introductionmentioning
confidence: 99%
“…Recently, cobalt (Co) has been successfully doped into the SnO 2 lattice and it was found that the doped samples exhibit a volume buffering effect and enhanced conductivity . In addition, the doped transition metal elements in electrode material can act as a catalytic media in corresponding electrochemical processes, reducing the reaction threshold and thus facilitating the reactions. In the field of microelectronic devices, element fluoride (F) has been widely applied to be doped into the lattice of SnO 2 to generate F doped tin oxide (FTO) as a universal substrate for various membrane deposition . In this regarding, it is found that insulated SnO 2 turns to be partly conductive after appropriate F doping.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polymeric citrate precursor route is insensitive to the presence of moisture and it does not require any inert atmosphere as well as even without careful control of the gel processing time, a high degree of homogeneity may be obtained in nanoproducts. Recently, this method has been used for the successful synthesis of Mn‐ and Co‐doped SnO 2 nanoparticles with controlled morphology . In this paper, we present our investigation to understand the structural, optical, and magnetic properties of Ni‐doped SnO 2 nanoparticles synthesized by modified solvothermal method through oxalate precursor route.…”
Section: Introductionmentioning
confidence: 99%